Singapore's citizen army : bridging the civil-military praxis - Ong, Wei Chong (2011)
Running against the grain of contemporary all-volunteer militaries, the Singapore Armed Forces remains predominately a national service conscript force. The citizen-soldier model must be retained to bind Singapore’s military and its society.!